Strategi Penyaluran Zakat Produktif PT. BPRS Artha Mas Abadi dalam Meningkatkan Pendapatan UMKM di Kabupaten Pati - Aqila, Felda Nur; Rohma, Alya Iftihatur; Ersa, Fina Alimatussolihah; Ahla, Azkiyatul; Kiftiah, Lailatul (JIOSE: Journal of Indonesian Sharia Economics, 2025)
This study aims to examine the strategy of productive zakat distribution by PT. BPRS Artha Mas Abadi in increasing the income of micro, small, and medium enterprises (MSMEs) in Pati Regency. The research method used a descriptive qualitative approach. Data were collected through interviews with BPRS, zakat collection partners, and MSME recipients. The study focused on the distribution mechanism, forms of collaboration, and the program's economic impact on beneficiaries. The results show that zakat distribution is carried out collaboratively, with 80% of the funds managed jointly by BPRS and zakat collection partners, and the remaining 20% ​​managed independently by zakat collection partners. This strategy has proven effective in increasing income, as seen by one zakat recipient who experienced a 40% increase in income. In addition to financial improvements, the program also encourages business motivation and strengthens economic capacity. These findings imply that productive zakat is not merely a temporary aid, but rather a long-term economic empowerment instrument that can encourage the independence of MSMEs at the local level.